Hill slope terrain and land-use assessment using GIS and Remote Sensing techniques: A case of Pikhuwa sub-watershed in the Mid-hill, Nepal - Rai, Dil Kumar; Lama, Furbe (Nepal Journal of Environmental Science, 2018)
Agriculture practice on hill-slope terrain depicts the sensitivity indicators of the vulnerability in terms of global climate change. The major aims of the present research are to assess the land-use pattern conditioned by existing hill-slope terrain based on different land capability class recommend by land resources mapping project, 1986 in the Pikhuwa sub-watershed of Mid-hills, Bhojpur, Nepal. An overall research data derived, processed and analyzed using Geographic Information System and Remote sensing tools and techniques. The land capability class, current land-use and digital elevation model with 30 meter spatial resolution have primarily considered as a major variable for spatial analysis. The analysis estimated about 33.68% individual area of overall agriculture patches have remained on above 30 degrees slope of the terrain topography, which denotes the condition of land-use is not suited technically based on land capability class and recommendation made by LRMP, 1986. In the sub-watershed, the current land-use condition on hill-slope is being much vulnerable due to the steep slope, poor slope terracing and unmanaged surface runoff during monsoon.